Potential role of platelets in COVID‐19: Implications for thrombosis - Milka Koupenova (Research and Practice in Thrombosis and Haemostasis, 2020)
Abstract For the past 150 years, platelets have been recognized as the major blood component that mediates hemostasis and thrombosis. In more recent years, however, we have come to appreciate that platelets also perform profound immune functions during infection with various pathogens. We now recognize that platelets can also mediate a response to various RNA viruses such as influenza and that many viral infections, including severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), can affect platelet count. Thrombocytopenia and increased coagulation have been independently associated with increased mortality. This article provides a perspective on the potential roles of platelets during coronavirus disease 2019.